Influences of the strategies of learning and the active reflectlon on the scholastlc yleld of the students of flfth year of secondary of the city of Lima - Escurra Mayaute, Luis Miguel (2004)
OBJECTIVE: To determine the influence of learning strategies and the active reflection on the academic performance of senior high school students of the city of Lima. DESIGN: Multivariate correlational study carried on Lima and Callao high school students of the 2003 class. INSTRUMENTS AND METHODS: A two stages conglomerate sampling afixed to size was used, resulting 1200 adolescents as participants. The ACRA scale was used and an Active Reflection scale was elaborated. The statistics analysis was done in three stages: A psychometric analysis to evaluate validity and reliability of ACRA's and Active Reflection scales, a descriptive analysis of the studied variables, and a multivariate (structural equation modeling) and bivariate analysis to test the hiphotesis. RESUL TS: The adolescents mean age was 16.1 year (with.±. 0.86 error aproximation). The 52% were female and the 48% were male. The students from public schools were the 53.8% and the ones from private schools were the 46.2%. Those from Lima were 61.1 %. CONCLUSIONS: The results indicated that both instruments, ACRA's and Active Reflection scales are valid and reliable. The students scores in both ACRA's and Active Reflection scales, and academic performance are normally distributed. There are significative differences in learning strategies and active reflection when each variable is analized considering school management. There are significative differences both in learning strategies and active reflection considering gender, also learning strategies and active reflection afects positively academic performance.